(untitled) (Contemporary Journal of Social Science Review, 2025)
The wide application of English language spans from schools and universities to social media and workspaces of Pakistan. British English has been traditionally taught in Pakistani classrooms because of the historical influence with British colonies in sub-continent. However, due to the extensive exposure to American media because of the dominant video media platforms like YouTube, Netflix, TikTok, and Instagram, may lead to incline students’ preferences toward American English over time. In this era of global media, this research investigates the attitudes of Pakistani university students, particularly ESL students toward British and American English. With the help of Language Attitudes Theory, this study examines how students use these varieties of English in informal as well as academic setting, utilizing qualitative approach. Data were collected through semi-structured interviews and a quick short assessment was conducted at the end of each interview with 40 English major students of the University of Okara. Results were drawn on the base of thematic analysis, which highlights the dominant use of British English due to institutional favoritism. But an extensive influence to American media, students showed a mixture use of both the varieties of English that highlights their change in taste, specifically in pronunciation and lexis choice. The research documents a disparity between formal education and use, providing important data to language teachers as well as curriculum planners to make the teaching of English more closely related to the changing linguistic realities of the learners.